تأثير تحسين زمن رد الفعل على أداء الضربة الدافعة بالوجه الأمامي في تنس الطاولة - زيزفون فادي; فاضل رغد; خير بك نوار (Latakia University Journal -Medical Sciences Series, 2016)
هدف هذا البحث هو تحسين زمن رد الفعل عند أداء الضربة الدافعة بالوجه الأمامي, تكونت عينة البحث من(24) مشارك، من لاعبي أندية الدرجة الأولى لتنس الطاولة في محافظة اللاذقية (فئة الناشئين), تم تقسيمهم إلى مجموعتين متساويتين (مجموعة تجريبية ومجموعة ضابطة), خضعت العينتين لاختبار قبلي لقياس زمن رد الفعل, وقاموا بأداء اختبار الكرة المدفوعة من الماكينة . ثم خضعت المجموعة التجريبية لبرنامج تدريبي مصمم لأربعة أسابيع: كل أسبوع مؤلف من ثلاث وحدات تدريبية وكل وحدة تتضمن أربعة أو خمسة تمارين لتطوير زمن رد الفعل في تنس الطاولة, بينما المجموعة الضابطة خضعت لبرنامجها التقليدي المعتادة عليه, ثم خضعت العينتان للاختبار البعدي, وأيضاً قاموا بأداء اختبار الكرة المدفوعة من الماكينة. استخدمت الباحثة المنهج التجريبي لمجموعتين (تجريبية وضابطة)، بإتباع القياس القبلي والبعدي لكلا المجموعتين. تمت مقارنة نتائج العينتين بين الاختبارين القبلي والبعدي, وأظهرت النتائج أن البرنامج التدريبي المطبق أثر إيجابياً على تحسين زمن رد الفعل عند أداء الضربة الدافعة بالوجه الأمامي. The aim of this research is to speed up the offensive tactic by improving reaction time when performing the forehand strike . For this reason, this research adopted the( 24) participants from the first-class table tennis clubs players in Latakia ( junior category ). They were divided into two equal groups (experimental and control group ) . The two samples underwent a pre test to measure reaction time , and they performed the ball driven from the machine test. Then, the experimental group underwent training program designed for four weeks : each week is composed of three training session and each session includes four or five exercises to develop the reaction time in table tennis . The control group underwent their traditional program as usual. Then the two samples underwent a post test , and they also performed the ball driven from the machine test. The searcher used experimental method for two groups (experimental and control) by using the pre and post test to the both groups. Then the results of the two samples were compared between pre and post tests . The researcher concluded that the applied training program affected positively on improving reaction time when performing the forehand strike .